Exploring Marine Planktonic Archaea: Then and Now - DeLong, Edward F. (Frontiers in Microbiology, 2021)
In 1977 Woese and Fox leveraged molecular phylogenetic analyses of ribosomal RNAs and identified a new microbial Domain of life on Earth, the Archaebacteria (now known as Archaea). At the time of their discovery, only one archaebacterial group, the strictly anaerobic methanogens, was known. But soon, other phenotypically unrelated microbial isolates were shown to belong to the Archaea, many originating from extreme habitats, including extreme halophiles, extreme thermophiles, and thermoacidophiles. Since most Archaea seemed to inhabit extreme or strictly anoxic habitats, it came as a surprise in 1992 when two new lineages of archaea were reported to be abundant in oxygen rich, temperate marine coastal waters and the deep ocean. Since that time, studies of marine planktonic archaea have revealed many more surprises, including their unexpected ubiquity, unusual symbiotic associations, unpredicted physiologies and biogeochemistry, and global abundance. In this Perspective, early work conducted on marine planktonic Archaea by my lab group and others is discussed in terms of the relevant historical context, some of the original research motivations, and surprises and discoveries encountered along the way.